Silent Remember Model in Adaptive Physical Education Learning for Deaf Students in SLB - Agustin Dwi Cahyani; Selvi Atesya Kesumawati; Muslimin Muslimin; I Bagus Endrawan (UNIB Press, 2024)
Adaptive physical education is physical education that is modified or adapted to make it easier for students with special needs to participate actively in adaptive physical education learning or modifications in adaptive physical education learning are aimed at making it easier for students to have equal opportunities to actively participate safely in enjoyable activities in learning. The aim of this research is to determine the results of developing the silent remember model in adaptive physical education learning for deaf students. The small group sample in this research consisted of 10 people and also involved 3 teachers as respondents, while the large group sample consisted of 20 people. The model development stages carried out are the model analysis, design, development, implementation and evaluation (ADDIE) stages. The instrument used in this research was a questionnaire. Expert validation test results using Content Validity Index (CVI) and Content Validity Ratio (CVR) in Silent Remember Learning with an average CVR value of 0.05. It can be interpreted that the silent remember model has high validity, which means that the silent remember model is safe to use according to the students' conditions and is good as a learning resource.